Multifunctional Operation and Application of GPS - Rustamov, Rustam B.; Hashimov, Arif M. (IntechOpen, 2018)
Today, Global Positioning System (GPS) has taken a significant place in human life with wide-scale applications. It is a multi-use, space-based radio-navigation system, embracing defense and security, civil, commercial, and scientific research needs. Taking into account the importance of the system, it has been suggested to present current advances of GPS with attention focused on vital aspects of technology. This book provides a general description of GPS, GNSS, and GLONASS with reference to the improvement of characteristics of the segments, including software applications and the equipment itself containing GPS. The book also provides information on application areas. Equally, a number of common shortcomings and errors are described, and elimination and mnimization of such consequences are demonstrated.